Using python to resolve the economic problems - Colesnicov, Alexandru; Malahov, Ludmila; Colesnicova, Tatiana; Verlan, Serghey (Artifex, 2019)
The work discusses the essential aspects of implementation of online economic applications using Python. The exemplified application performs econometric calculations over the data on an enterprise to analyze situation on labour market. Calculations include data grouping and statistics, extended Mincer earnings function, Duncan index of dissimilarity, the Oaxaca-Blinder decomposition.
Text: lb. engl. Abstract: lb. engl. Referinţe bibliografice: pp. 448-449 (12 titl.). JEL Classification: C02, C80, C88, C89.
Keywords: online economic applications; Python; econometric calculations; labour market